MINAT BELAJAR BAHASA ARAB SISWA MINAT BELAJAR BAHASA ARAB SISWA MELALUI MODEL MUHADATSAH YAUMIYYAH SMAN 1 SIAK: MUHADATSAH YAUMIYYAH - WANTI, DESY (Universitas Negeri Malang, 2022)
This study aims to increase students' interest in learning Arabic through the application of the Muhadatsah Yaumiyyah model. This research is a classroom action research. The research subjects were students of class XI IPA 1 SMAN 1 Siak, totaling 32 people. In this study the data obtained through observation. Data analysis was carried out with a qualitative descriptive with a percentage technique. The results showed that the application of the Muhadatsah Yaumiyyah Model in learning Arabic could increase students' interest in learning. In the first cycle the interest of students who have an interest in learning amounted to 61.8% with the category